Basal Settings Control Fast Ice Flow in the Recovery/Slessor/Bailey Region, East Antarctica - Diez, Anja; Matsuoka, Kenichi; Ferraccioli, Fausto; Jordan, Tom A; Corr, Hugh F; Kohler, Jack; Olesen, Arne V; Forsberg, René (Geophysical Research Letters, 2018)
The region of Recovery Glacier, Slessor Glacier, and Bailey Ice Stream, East Antarctica, has remained poorly explored, despite representing the largest potential contributor to future global sea level rise on a centennial to millennial time scale. Here we use new airborne radar data to improve knowledge about the bed topography and investigate controls of fast ice flow. Recovery Glacier is underlain by an 800 km long trough. Its fast flow is controlled by subglacial water in its upstream and topography in its downstream region. Fast flow of Slessor Glacier is controlled by the presence of subglacial water on a rough crystalline bed. Past ice flow of adjacent Recovery and Slessor Glaciers was likely connected via the newly discovered Recovery-Slessor Gate. Changes in direction and speed of past fast flow likely occurred for upstream parts of Recovery Glacier and between Slessor Glacier and Bailey Ice Stream. Similar changes could also reoccur here in the future.
Keywords: Antarktis; geofysikk; geologi; glasiologi; havnivåstigning; isbre; isstrøm

Topographic Steering of Enhanced Ice Flow at the Bottleneck Between East and West Antarctica - Winter, Kate; Ross, Neil; Ferraccioli, Fausto; Jordan, Tom A; Corr, Hugh F J; Forsberg, René; Matsuoka, Kenichi; Olesen, Arne V; Casal, Tania G (Geophysical Research Letters, 2018)
Hypothesized drawdown of the East Antarctic Ice Sheet through the “bottleneck” zone between East and West Antarctica would have significant impacts for a large proportion of the Antarctic Ice Sheet. Earth observation satellite orbits and a sparseness of radio echo sounding data have restricted investigations of basal boundary controls on ice flow in this region until now. New airborne radio echo sounding surveys reveal complex topography of high relief beneath the southernmost Weddell/Ross ice divide, with three subglacial troughs connecting interior Antarctica to the Foundation and Patuxent Ice Streams and Siple Coast ice streams. These troughs route enhanced ice flow through the interior of Antarctica but limit potential drawdown of the East Antarctic Ice Sheet through the bottleneck zone. In a thinning or retreating scenario, these topographically controlled corridors of enhanced flow could however drive ice divide migration and increase mass discharge from interior West Antarctica to the Southern Ocean.
Keywords: Antarktis; glasiologi; innlandsis; isgjennomtrengende; isstrøm; radarundersøkelser

Patchy Lakes and Topographic Origin for Fast Flow in the Recovery Glacier System, East Antarctica - Diez, Anja; Matsuoka, Kenichi; Jordan, Tom A; Kohler, Jack; Ferraccioli, Fausto; Corr, Hugh F; Olesen, Arne V; Forsberg, René; Casal, Tania G (Journal of Geophysical Research: Earth Surface, 2019)
The Recovery subglacial basin, with its largest glacier Recovery Glacier, has been identified as potentially the biggest contributor to future sea level rise from East Antarctica. Subglacial lakes along the main trunk have been detected from satellite data, with four giant lakes (Recovery Lakes A, B, C, and D) located at the onset of the fast ice flow (≥15 m/yr) and multiple smaller lakes along the glacier. The presence of subglacial water potentially plays a key role in the control of fast ice flow of Recovery Glacier. We present new insights on the Recovery Lakes from airborne radar data collected in 2013 and 2015. Using an adjusted classification scheme, we show that a single large area consisting of smaller lakes connected by likely saturated sediment, referred to as Lake AB, exists in the originally proposed area of the Recovery Lakes A and B. We estimate that the current size of Lake AB is ∼4,320 km2. Water likely leaks from the western shore of Lake AB lubricating the bed initiating fast ice flow at this location. The difference in the outlines of Lake AB and the Lakes A and B previously derived from surface features suggested that a larger paleolake existed here in the past. From our data, we find Recovery Lake C to be dry; we attribute fast ice flow originating from this area to be due to a topographic step and thus an increase in ice thickness rather than enhanced lubrication at the bed.
Keywords: Antarktis; glasiologi; havnivåstigning; innlandsis; radar observasjoner; satellite bilder; subglasial innsjø; topografi

Bedmap3 updated ice bed, surface and thickness gridded datasets for Antarctica - Pritchard, Hamish D.; Fretwell, Peter T.; Fremand, Alice C.; Bodart, Julien A.; Kirkham, James D.; Aitken, Alan; Bamber, Jonathan; Bell, Robin; Bianchi, Cesidio; Bingham, Robert G.; Blankenship, Donald D.; Casassa, Gino; et al. (Scientific Data, 2025)
We present Bedmap3, the latest suite of gridded products describing surface elevation, ice-thickness and the seafloor and subglacial bed elevation of the Antarctic south of 60 °S. Bedmap3 incorporates and adds to all post-1950s datasets previously used for Bedmap2, including 84 new aero-geophysical surveys by 15 data providers, an additional 52 million data points and 1.9 million line-kilometres of measurement. These efforts have filled notable gaps including in major mountain ranges and the deep interior of East Antarctica, along West Antarctic coastlines and on the Antarctic Peninsula. Our new Bedmap3/RINGS grounding line similarly consolidates multiple recent mappings into a single, spatially coherent feature. Combined with updated maps of surface topography, ice shelf thickness, rock outcrops and bathymetry, Bedmap3 reveals in much greater detail the subglacial landscape and distribution of Antarctica’s ice, providing new opportunities to interpret continental-scale landscape evolution and to model the past and future evolution of the Antarctic ice sheets.
Article Number: 414
Keywords: Antarktis; geofysikk; geomorfologi; glasiologi; hydrologi; oseanografi